Dissecting Factors Causing Active Behaviors Associated with Continuity of Youth Participation in Agro-Preneurship : A Qualitative Study on Youth Farmers in Sarawak - Abdul Rahman, Saili; Jamayah, Saili; Mazia, Mohamad Safai’ee; Nur Masriyah, Hamzah (Universal Publishers - Boca Raton, Florida, USA, 2018)
Purpose: Despites of an aggressive growth of agricultural sectors, the number of youth participating in the industry is low. Agriculture as one of the main income generator industry should be exposed to the community in order to raise and encourage the participating of the community and also for the development of the industry. Thus, this research is conducted using a qualitative study to understand and dissecting the youth behavior toward their activities in agropreneurship. Design/methodology/approach: Data from six in-depth interviews were analysed to explore the experience of youth agro-preneurs. Findings: The result indicated that the two major groups of behaviors dictated the acceptances of youth toward agro-preneurship in Sarawak are psychological factors and economic factor. Practical implications: The findings of this paper will help to boast the agro-preneurship activities among youth in Malaysia. In response to increase youth participation in agriculture is more important than ever, as the burgeoning global population and decreasing agriculture productivity mean the youth must play pivotal role in ensuring a food-secure future for themselves, and for future generations. Originality/value: This paper managed to explore deeper insights on how the psychological and economic factor plays a pivotal role to sustain the involvement of youth farmers in agricultural industry. It also highlights on how to attract youth participation in agro-preneurship in Malaysia.